MUSLIMAH WORK CLOTHING ANALYSIS - pingki indrianti (UIN Syarif Hidayatullah Jakarta, 2019)
Abstract. The phenomenon of trends and the increasing number of headscarves in Indonesia is accompanied by an increasing number of female workers who wear headscarves, especially in a number of formal offices in big cities, both private and government agencies. However, formal Muslim work attire today in general, many are just following the trend without regard to the suitability of the function of work clothes and in terms of Islamic sharia. This research was conducted to look for criteria or standardization of Muslim work attire, both in terms of silhouette and material usage. The analysis was conducted on the types of formal and semi-official clothing in the formal sector work environment, namely by using a number of pictures or photographs of Muslim women's work clothes from personal documentation, magazines, and online trading sites. Each picture is then given points 1-5 based on the criteria for the function of work clothes and Islamic sharia. The Islamic sharia concept which is used as a reference in assessing the limits of the aahah of Muslim clothing, is the interpretation of Islam to the traditionalists and modernists in Indonesia. The results of the analysis are grouped into three with the highest point value of four to five points. There are Muslim work clothes in accordance with Islamic sharia but do not approach the basic concept of work clothes, Muslim work clothes that are in accordance with the concept of work clothes but do not suffice for sharia values, and Muslim work clothes that meet the value of both.Abstrak. Fenomena tren dan meningkatnya pengguna jilbab di Indonesia diiringi dengan meningkatnya jumlah pekerja wanita yang menggunakan jilbab khususnya pada sejumlah perkantoran formal di kota besar baik instansi swasta maupun pemerintahan. Namun demikian busana kerja muslim formal saat ini pada umumnya banyak yang hanya mengikuti tren tanpa memperhatikan kesesuaian fungsi busana kerja maupun dari segi syariah Islam. Penelitian ini dilakukan untuk mencari kriteria atau standarisasi gaya busana kerja muslim, baik dari segi siluet maupun penggunaan material. Analisis dilakukan pada jenis busana resmi maupun setengah resmi pada lingkungan pekerjaan sektor formal, yaitu dengan menggunakan sejumlah gambar atau foto busana kerja muslim wanita baik yang berasal dokumentasi pribadi, majalah, serta situs jual-beli online. Setiap gambar kemudian diberikan poin 1-5 berdasarkan kriteria fungsi busana kerja dan syariah Islam. Adapun konsep syariah Islam yang digunakan sebagai acuan dalam menilai batasan aurat busana muslimah, adalah penafsiran Islam pada kaum tradisionalis dan modernis di Indonesia. Hasil analisis dikelompokan menjadi tiga dengan nilai poin tertinggi yaitu empat sampai dengan lima poin. Terdapat busana kerja muslimah sesuai dengan syariah Islam namun tidak mendekati konsep dasar busana kerja, busana kerja muslimah yang sesuai konsep busana kerja namun tidak mencukupi nilai syariah, serta busana kerja muslimah yang mencukupi nilai keduanya.